Evaluation of the Young Deadly Free Peer Education Training Program: Early Results, Methodological Challenges, and Learnings for Future Evaluations - D'Costa, Belinda; Lobo, Roanna; Thomas, Jessica; Ward, James Steven (Frontiers in Public Health, 2019)
Australian Aboriginal and Torres Strait Islander people experience disproportionately higher rates of sexually transmissible infections (STIs) and blood borne viruses (BBVs) when compared with the non-Indigenous population. Both incidence and prevalence data for bacterial STIs, such as chlamydia, gonorrhoea, trichomonas, and syphilis in remote areas of Australia are reported at rates many times higher than that of non-Indigenous Australians. Similarly, rates of hepatitis B are disproportionately higher for non-Indigenous people in remote communities. The Young Deadly STI and BBV Free project was designed to increase the uptake of STI and BBV testing and treatment in young Aboriginal and Torres Strait Islander people living in remote and very remote areas of South Australia, Western Australia, Queensland, and the Northern Territory. Peer education formed one component of this pilot project and involved training up to 100 young Aboriginal and Torres Strait Islander people across 19 communities in a culturally appropriate and respectful manner on the transmission, testing, and treatment of STIs and BBVs. The trained peer educators were then required to deliver three community education sessions to young people in their respective communities in an effort to raise awareness about STIs and BBVs and encourage testing and treatment uptake. Preliminary evaluation findings, limited to the trained peer educators, revealed the peer educator training program contributed to STI and BBV knowledge gains among the trained peer educators and positively influenced their behavioural intentions and attitudes pertaining to STIs and BBVs. Working with remote Aboriginal and Torres Strait Islander populations on a highly sensitive, stigmatised topic presented many methodological challenges, particularly in terms of ensuring the collection of reliable evaluation data across geographically remote communities.. The challenges and strengths associated with the implementation of the peer education training program along with implications for developing culturally inclusive evaluation practices will be discussed.